2018
DOI: 10.17706/ijeeee.2018.8.3.154-164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Telecommunication Companies Using Data Envelopment Analysis: Toward Efficiency of Mobile Telephone Operator in Tanzania

Abstract: The mobile telephone sector has shown dramatic growth in Africa. With the number of mobile phone operators raised, now Tanzania considered the largest telecommunications network in East Africa with over 40 million registered subscribers and mobile money accounts. However, the services provided by operators have not been assessed by the Authority. Therefore, this paper focus on evaluating the efficiency of mobile phone operators in Tanzania. A data envelopment analysis (DEA), NonRadial and Oriented model on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Telkom achieved efficiency = 1 (constant return scale) in 2019 and 2020, Link Net in 2015, Icon Plus in and 2017, Moratel in 2015and 2017, and Bali Towerindo in 2017, 2017, 2019, Link Net was one of the operators experiencing declining returns to scale (drs). It occurred to Icon Plus in 2018, 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telkom achieved efficiency = 1 (constant return scale) in 2019 and 2020, Link Net in 2015, Icon Plus in and 2017, Moratel in 2015and 2017, and Bali Towerindo in 2017, 2017, 2019, Link Net was one of the operators experiencing declining returns to scale (drs). It occurred to Icon Plus in 2018, 2019.…”
Section: Resultsmentioning
confidence: 99%
“…The SFA method was used by Riko et al (2019) to conduct a technical efficiency analysis, which revealed that telecommunication companies in Asia Pacific have lower technical efficiency than those in developed countries. Suleiman et al, 2017) determined that only three (three) cellular phone operators out of seven (seven) operators studied were efficient using Data Envelopment Analysis (DEA), Non-Radial and Oriented Model on Slack-based Measure (Devaki, 2020), the financing pattern of telecommunication service companies provides analysis results that describe the company's capital structure, which is important to maintain a good solvency position. Kayisire & Wei (2016) evaluated the efficiency of mobile phone operators using DEA to measure various benchmarking industries and evaluate the performance of Information and Communication Technology (ICT) adoption in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have worked on the performance evaluation of MNOs. An example is the performance evaluation of Tanzania's MNOs (Sulaiman, Hemed, & Wei, 2018). The study evaluated the performance of MNOs using Data Envelopment Analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Suleiman, Hemed and Wei (2017) evaluate the efficiency of 7 mobile operators in Tanzania from 2010 to 2016. The methodology applied was the Non-Radial Slack-Based Measure (SBM) Data Envelopment Analysis (DEA) in each operator.…”
Section: Literature Reviewmentioning
confidence: 99%